Pattern adjustments to simulate the fall of the fabric tweed - Muan, Mariane Baginda; Escano, Maria Monica R. (2006.)
Different fabrics are used for different designs of garments. When designing a garment, knowledge of both draping and flat patternmaking is crucial. "Flat pattern cutting is successful when a mental process of transformation can give the designer an intuitive knowledge of the 3D fabric shape produced by the pattern (Aldrich, 20)." It is also important to have knowledge on fabrics to be able to foresee the appearance or hang of the fabric when sewn into a garment and fitted on to a figure. The main objective of the study was to determine the fall of different fabrics using one design. Specifically, it visualized the hang of the chosen fabrics using only one pattern and on dress form. It also determined whether the differences in weave and weight affect the drape of fabrics, and, determined how much fabric should be adjusted to achieve the fall of tweed using pattern manipulation. This study was conducted to give a view of what fabrics of the same drapability and same pattern but different weave constructions and weights look like. It also gave designers an idea on how to achieve the fall of fabric using another fabric by manipulating the pattern. Five fabrics were chosen for this study. These fabrics were seersucker, twill, chiffon, georgette, and tweed. They were cut and sewn into a semi-circular skirts using one pattern. The fabrics chiffon, georgette, seersucker, and twill were chosen to simulate the fall or hang of tweed. The results revealed that the patterns should be reduced in able to achieve the silhouette of tweed and to simulate its flares. The researcher recommends to also study the use of different styles of skirts can also be done. Knitted fabrics and non-textile fabrics like film, leather, and fur could be used as medium to give a wider range of information.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Dressmaking -- Pattern design